Integrating Medicinal Pathology by Exploring Capsaicin-Based Therapies into Gynecologic Oncology Practice: A Meta-Analysis - Abdul Ghafoor; Umme Habiba; Syed Azhar Hussain Zaidi; Aisha Altaf; Durga Devi; Asma Hamid; Amanullah Bukhari (Pakistan Journal of Medicine and Dentistry)
Background: The bioactive component present within chili peppers, capsaicin, has shown anticancer effects in multiple cancers, including cervical cancer, ovarian cancer, and uterine cancer. It induces apoptosis, disrupts the proliferation of the cancer cell, and modulates pathways such as NF-κB, PI3K/Akt, and p53. This work examines the effect of capsaicin on gynecology-based cancer cells to determine their therapeutic potential and influence on tumor progression and the cellular response.